x 3 + 1 6 x + 1 7 5 = 0
The equation above has roots α , β and γ . Find the value of the expression below.
γ α + β α + β γ + α γ + α β + γ β
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice solution! I would've done it with transformation but your method is much clever.
My method actually looks a bit longer than it is, because I explained it in a really detailed manner, but yours is indeed shorter. Nice!
Did exact same. Overrated.
Did the same way.
My method resembles to that of tanishq but here's how I approached
For the convenience of my typing I am taking roots as a,b,c.
a+b+c=0
Summing the expression given we get
z x + y + x y + x + y z + x
adding 3 and subtracting 3 we get
(x+y+z) x 1 + y 1 + z 1 -3
Since x+y+z=0 so value of the expression is − 3
Let γ α + β α + β γ + α γ + α β + γ β = S
Multiplying S by α β γ :
α β γ S = α 2 β + α 2 γ + γ 2 α + γ 2 β + β 2 γ + β 2 α
= α β ( α + β ) + α γ ( α + γ ) + β γ ( β + γ )
= α β ( α + β + γ − γ ) + α γ ( α + γ + β − β ) + β γ ( β + γ + α − α )
By Vieta's, α β γ = − 1 7 5 and α + β + γ = 0 , so:
− 1 7 5 S = α β ( 0 − γ ) + α γ ( 0 − β ) + β γ ( 0 − α )
= α β ( − γ ) + α γ ( − β ) + β γ ( − α )
⟹ − 1 7 5 S = − 3 α β γ = 5 2 5
⟹ S = − 1 7 5 5 2 5 = − 3
I have got a shorter method
C l e a r l y t h e s u m o f r o o t s i s z e r o ⇒ α + β + γ = 0 ( 1 ) α 1 + β 1 + γ 1 = ? ( 2 ) ( 1 ) × ( 2 ) ( α + β + γ ) ( α 1 + β 1 + γ 1 ) = 1 + β α + γ α + α β + 1 + γ β + α γ + β γ + 1 ⇒ 0 = β α + γ α + α β + γ β + α γ + β γ + 3 ⇒ β α + γ α + α β + γ β + α γ + β γ = ( − 3 )
Nice solution but what if the question I gave you did include a coefficient for x 2 ? What would've you done then.
Problem Loading...
Note Loading...
Set Loading...
clearly sum of roots is zero.
α + β + γ = 0
α + β = − γ ...... ( 1 )
α + γ = − β ......... ( 2 )
β + γ = − α ......... ( 3 )
Rearranging the given expression
γ α + β + β α + γ + α β + γ
From ( 1 ) , ( 2 ) , ( 3 )
γ − γ + β − β + α − α
=> − 1 − 1 − 1 = − 3